2006
DOI: 10.1084/jem.20052230
|View full text |Cite
|
Sign up to set email alerts
|

A dose-dependent requirement for the proline motif of CD28 in cellular and humoral immunity revealed by a targeted knockin mutant

Abstract: Activation of naive T cells requires the integration of signals through the antigen receptor and CD28. Although there is agreement on the importance of CD28, there remains controversy on the mechanism by which CD28 regulates T cell function. We have generated a gene-targeted knockin mouse expressing a mutation in the C-terminal proline-rich region of the cytoplasmic tail of CD28. Our analysis conclusively showed that this motif is essential for CD28-dependent regulation of interleukin 2 secretion and prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 55 publications
3
76
0
Order By: Relevance
“…1B and C). These results complement previous data demonstrating that the Lck-binding motif is also required during co-stimulation, and that TCR signals cannot compensate for defective signalling through CD28 that cannot bind Lck [4,7,20,21]. Cells expressing CD28 with a tyrosine-to-phenylalanine mutation in the YMNM motif, which recruits both PI3K and Vav1, did not proliferate following stimulation through CD28, but proliferated comparably to wild-type cells following PMA1ionomycin stimulation ( Fig.…”
Section: Cd28-mediated Proliferation Requires Integrity Of the Ymnm Asupporting
confidence: 78%
“…1B and C). These results complement previous data demonstrating that the Lck-binding motif is also required during co-stimulation, and that TCR signals cannot compensate for defective signalling through CD28 that cannot bind Lck [4,7,20,21]. Cells expressing CD28 with a tyrosine-to-phenylalanine mutation in the YMNM motif, which recruits both PI3K and Vav1, did not proliferate following stimulation through CD28, but proliferated comparably to wild-type cells following PMA1ionomycin stimulation ( Fig.…”
Section: Cd28-mediated Proliferation Requires Integrity Of the Ymnm Asupporting
confidence: 78%
“…Consistent with this result, a mutation in the C-terminal proline-rich region of the cytoplasmic tail of CD28 showed that this motif is essential for CD28-dependent regulation of IL-2 secretion and T cell proliferation. In vivo analysis revealed that mutation of this motif dissociated the CD28-dependent regulation of cellular and humoral responses in an allergic airway inflammation model (52). From the transcription level, the NIK regulates IL-2 synthesis by activating the CD28 responsive element (CD28RE) of the IL-2 promoter and strongly synergizes withc-Rel in this reaction, by interacting with the N-terminal domain of c-Rel through phosphorylating the C-terminal transactivation domain (TAD) of c-Rel and inducing Gal4-c-Rel-transactivating activity (53).…”
Section: Intracellular Signals Of Costimulation In T Cell Responsementioning
confidence: 99%
“…Using a closely matched set of CD28 transgenes that restored CD28 expression in CD28 Ϫ/Ϫ mice to physiologic levels but that encoded CD28 molecules with disruptions in different cytosolic binding motifs, we have documented that the CD28 costimulatory signals required for in vivo IL-2 production and T regulatory (Treg) cell generation in the thymus were strictly dependent on an intact Lck binding site in the CD28 cytosolic tail (12). The importance of an intact Lck binding site for CD28 costimulation has since been confirmed for in vivo humoral immune responses by mice constructed with a gene knockin mutation of the C-terminal proline motif in the CD28 cytosolic tail (13).…”
mentioning
confidence: 94%
“…It is interesting that the same C-terminal proline motif in the CD28 cytosolic tail that we have now shown to be required for in vivo autoimmune disease induction in CTLA-4-deficient mice was previously shown to be critical for in vivo generation of Treg cells, in vivo stimulation of IL-2 production, and in vitro T cell proliferative responses (7,12,13,20). As a result we think that the Lck binding motif in the CD28 cytosolic tail is especially important for CD28-mediated costimulation of TCR-signaled thymocytes and T cells.…”
Section: Ctla-4mentioning
confidence: 99%